A concepção de Emmanuel Levinas sobre a morte: a crítica ao ser-para-morte da filosofia heideggeriana - Mendes, Anderson Fernando Rodrigues (2015)
This paper aims to investigate the subject of death from the French-Lithuanian philosopher Emmanuel Levinas approach, based on his works Totalité et Infini (1961) - with translation into Portuguese - and Dieu, la mort et le temps (1993) - in its translation into Spanish - dialogue with the German philosopher work, Martin Heidegger, titled Being and Time (1927). Probably Levinas is one of the most debated philosophers on century XXI and, for belonging to a Jewish family, educated according to their religious tradition, its philosophical approach proves pertinent to our reflection. This research delimits the study and reflection on the theme of death, because this issue has not its importance only to the religious and philosophical reflections, but for the man as being who lives as a whole. The relevance of this research is the reflection of the meaning of death for humans, as a being that lives beyond the shrouded emotional consequences on death phenomenon as anguish, fear and ignorance. Levinas goes into an intensive dialogue with Heidegger's philosophy and his approach about death and its impact on man. This research is divided into three parts: the first part of this study will deal with the introduction of the author, or his person, his time and his work; in the second part of this study, we will discurss the concept of death to the philosopher with whom Levinas more dialogues in work Dios, la muerte y el tiempo, Martin Heidegger and his being-toward-death. Here, we will discurss the finiteness of Dasein, Heidegger's ontological project as well as anguish, fear and the most authentic existential possibilities of being; the third part of our proposition studies, we will launch the themes of reflection regarding the death in Levinasian philosophy. In this part, we will reflect about our death, the death of the Other and issues surrounding the death of the subject, such as anxiety, fear and infinity. The methodology that will be applied to this research is based on analysis of Levinasian reflection from de Dios, la muerte y el tiempo, Totality and Infinity of Emmanuel Levinas and Heidegger Being and Time. The aim of this work contribute to the studies in the Sciences of Religion, Philosophy of Religion and Theology as well as in other related areas.